Prevalence and treatment of diabetes mellitus and hypertension among older adults with intellectual disability in comparison with the general population. Issue 1 (December 2017) - Axmon, Anna; Ahlström, Gerd; Höglund, Peter
Abstract Background Diabetes mellitus and hypertension are risk factors for cardiovascular disease, which is the most common cause of death in the world. People with intellectual disability (ID) have been reported to have high rates of both these disorders. The aim of this study was to describe and compare prevalence ratios of diabetes mellitus and hypertension between older adults with ID and their age peers in the general population, and to describe and compare treatment patterns in these two groups. Methods This is a Swedish register-based study, in which we established a cohort of people aged 55+ years and who had received support for those with ID in 2012 (n  = 7936). We also established a same-sized referent cohort from the general population matched by sex and year of birth. Information on diagnoses of diabetes mellitus and hypertension, and prescription of drugs for these disorders, were collected from national registers for the period 2006–2012. The two cohorts were compared using generalized linear models (GLM). Results People with ID were 20% more likely than the general population to have a diagnosis of diabetes mellitus, and 26% more likely to have prescription of drugs for diabetes mellitus. People in the general population were 81% more likely to have a diagnosis of hypertension, and 9% more likely to have a prescription of drugs for hypertension. Among those with diabetes, ID was associated with higher occurrence of prescription of insulin combination drugs and sulfonylureas, but lower occurrence of prescription of dipeptidyl peptidase (DPP) 4-inhibitors and exenatide/liraglutide. Among those with hypertension, ID was associated with higher occurrence of prescription of diuretics, but lower occurrence of prescription of calcium channel blockers and angiotensin II antagonists. Conclusions Treatment regimens among people with ID tended to include older types of medication compared with what was prescribed in the general population. To ensure that this is medically appropriate and not due to failure to update the treatment regimen, it is important to investigate if the people with ID and diabetes mellitus or hypertension are subjected to the same regular drug reviews that are recommended for older adults in general.